A) \[x=-3,-2\]
B) \[x=3,2\]
C) \[x=-3,2\]
D) \[x=3,-2\]
Correct Answer: D
Solution :
[d] Let \[{{3}^{x}}^{^{2}}=a\] and \[{{3}^{x+6}}=b\] the given equation reduces to \[{{a}^{2}}-2ab+{{b}^{2}}=0\] \[\Rightarrow \] \[{{(a-b)}^{2}}\] \[\Rightarrow \] \[a=b\] \[\therefore \] \[3{{x}^{2}}={{3}^{x+6}}\] \[[{{a}^{m}}={{a}^{n}}\,\,\,\,then\,\,\,\,m=n]\] \[\Rightarrow \] \[{{x}^{2}}=x+6\] \[\Rightarrow \] \[{{x}^{2}}-x-6=0\] \[\Rightarrow \] \[{{x}^{2}}-3x+2x-6=0\] \[\Rightarrow \] \[x(x-3)+2(x-3)=0\] \[\Rightarrow \] \[(x-3)(x+2)=0\] \[\Rightarrow \] \[x=3\,or\,x=-2\]You need to login to perform this action.
You will be redirected in
3 sec